Perancangan Sistem Informasi Pengolahan Data Kependudukan Berbasis Website Desa Penggung Boyolali - Haidar Fiki Rabani; Ina Sholihah Widiati; Tinuk Agustin; Hadis Turmudi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The use of information technology is increasingly advanced in the 4.0 era, especially in the field of village government. The purpose of the web-based population data processing information system for Penggung Village, Boyolali, is to have a good impact on population data management. The problems faced, such as conventional data archiving that causes data accumulation and corruption, drive the need for this solution. The prototype development method was chosen because it provides high interactivity between users and developers. The system is equipped with features of population data management, automatic archiving, quick search, and CRUD function. The results of the study show that this system increases the efficiency and speed of information access and reduces the risk of data loss and corruption. The implementation of this web-based information system is expected to be an effective solution for the village government and provide a new perspective for future research.